Pre-trabeculectomy intravitreal injections of bevacizumab for treating neovascular glaucoma in diabetic patients - Marjanović, Ivan; Marjanović, Marjan; Gvozdenović, Ranko; Marjanović, Marija; Marković, Vujica; Božić, Marija; Marić, Vesna; Martinez, Antonio (Vojnosanitetski pregled, 2021)
Background/Aim. Neovascular glaucoma (NVG) is a secondary glaucoma caused by occlusion of the trabecular network of newly formed blood vessels. The aim of this study was to evaluate the efficacy and safety of intravitreal injections of bevacizumab before trabeculectomy with mitomycin C (MMC) for the treatment of NVG. Methods. A prospective and open-label study was conducted from May 2013 to December 2014 on consecutive NVG patients who underwent intravitreal injections of bevacizumab and a primary trabeculectomy with MMC. All patients were followed-up at least for 12 months. Success was defined as an intraocular pressure (IOP) of ≤ 21 mm Hg with or without topical ocular hypotensive medication. Results. Fourteen eyes of 12 diabetic patients fulfilled the respective demands of the inclusion and exclusion criteria. The mean (± standard deviation) follow-up period was 15.0 (± 2.0) months (range, 12 to 19 months). After one year of follow-up, 11 (78.6%) eyes had an IOP ≤ 21 mmHg. The mean IOP was significantly reduced from 42.4 (± 9.7) mmHg preoperatively to 18.4 (± 2.9) mmHg postoperatively (p < 0.0001). Regarding surgical complications, 6 months of trabeculectomy, hyphaema was observed in 3 (21.4%) eyes, macular edema in one (7.1%) eye and recurrence of neovascularization requiring intravitreal bevacizumab injection in 2 (14.2%) eyes. Conclusion. Preoperative intravitreal bevacizumab may be effective as adjunctive treatment for trabeculectomy with mitomycin-C for neovascular glaucoma patients.